Enzymatic Protein Hydrolysate from Tuna Canning Wastes - Standardisation of Hydrolysis Parameters - M.R., Raghunath (Fishery Technology, 2025)
Tuna canning wastes, consisting of cooked tuna red meat was hydrolysed using pineapple juice as a source of crude Bromelain. Optimum conditions for hydrolysis as monitored by solids and nitrogen solublllzatlon were: 0.(X)8 units enzyme/mg substrate protein, 5-6 pH and 60-70Â°C temperature. Substrate concentration did not appear to have much influence on solubilizatlon of solids. Material balance tmder optimized conditions of hydrolysis showed that soluble solids and soluble nitrogen increased by 62.6 and 92% respectively over initial levels and could be recovered with minimal losses.